2018
DOI: 10.1002/jbm.a.36493
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of resveratrol and resveratrol‐functional selenium nanoparticles: Inhibiting amyloid β aggregation and reactive oxygen species formation properties

Abstract: Deposition of amyloid‐β (Aβ) aggregates and formation of neurotoxic reactive oxygen species (ROS) are significant pathological signatures of Alzheimer's disease (AD). Resveratrol (Res) is an antioxidant with the potential to treat AD. However, the bioavailability and solubility of Res is very low and it cannot entirely inhibit Cu2+‐induced Aβ42 aggregation at low concentration. Herein, we combine the unique Aβ absorption property of selenium nanoparticles with the natural antioxidant agent Res to form Res@SeNP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 44 publications
1
44
0
Order By: Relevance
“…Several authors have reported interesting results concerning the use of SeNPs as a therapeutic agent for neurodegenerative diseases . Several works demonstrated that SeNPs are able to reduce Aβ aggregation and prevent Aβ‐induced toxicity in PC12 cells . In another work, SeNPs were able to reduce neuronal death, ROS levels, and behavioral disorders in a C. Elegans in vivo model of HD, by reducing also the aggregation of huntingtin protein .…”
Section: Inorganic Nano‐antioxidants For Biomedical Applicationsmentioning
confidence: 99%
“…Several authors have reported interesting results concerning the use of SeNPs as a therapeutic agent for neurodegenerative diseases . Several works demonstrated that SeNPs are able to reduce Aβ aggregation and prevent Aβ‐induced toxicity in PC12 cells . In another work, SeNPs were able to reduce neuronal death, ROS levels, and behavioral disorders in a C. Elegans in vivo model of HD, by reducing also the aggregation of huntingtin protein .…”
Section: Inorganic Nano‐antioxidants For Biomedical Applicationsmentioning
confidence: 99%
“…[13][14][15] Besides, resveratrol has multiple bioactivities of antioxidants, antiaging, insulin sensitization and plays a critical role in many diseases. [16][17][18] Several reports have showed that resveratrol was capable of decreasing the levels of blood glucose in diabetic rats, normal rats and mice and humans. 19,20 Resveratrol can interact with multiple molecular targets which are related to inflammation and immunity.…”
mentioning
confidence: 99%
“…Likewise, the same group designed SeNPs modified with resveratrol and tested their properties against ion metal-induced A β 42 aggregation. They obtained similar effects as described above, i.e., that resveratrol and SeNPs exhibit synergistic effect regarding the inhibition of pathological protein aggregation [ 54 ]. A nanocomposite engineered from quercetin, SeNPs, and polysorbate 80 can serve as another example of SeNPs combined with antioxidants.…”
Section: Nanoparticles As Therapeutics Of the Futurementioning
confidence: 67%